Analisis Growth Opportunity, Leverage, Likuiditas, Dan Firm Size Terhadap Keputusan Hedging Pada Perusahaan Perbankan - Cindy Apriliani; Diah Yudhawati; Angga Prasetia (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study aims to determine the effect of growth opportunity, leverage, liquidity, and firm size on hedging decisions in banking companies listed on the Indonesia Stock Exchange during the 2019-2023 period. The data used is secondary data obtained from the Indonesia Stock Exchange. The sample selection was carried out using purposive sampling technique, where 15 companies that met the criteria were selected based on characteristics relevant to the research objectives. The research method used is logistic regression analysis because the data used are metric and non-metric. The results of simultaneous testing, based on the Omnibus Test of Model table, show that there is a significant influence of growth opportunity, leverage, liquidity, and firm size on hedging decisions in banking companies. Partially, the growth opportunity variable has no effect on hedging decisions in banking companies. The leverage variable has a significant effect on hedging decisions in banking companies. The liquidity variable has a significant positive effect on hedging decisions in banking companies. The firm size variable has a significant positive effect on hedging decisions in banking companies.